THE ROLE OF NAPOSO NAULI BULUNG IN PRESERVING BATAK MANDAILING CULTURE IN BANGAI VILLAGE, TORGAMBA DISTRICT, SOUTH LABUHANBATU REGENCY - Syaiful Amry Harahap; Syarbaini Saleh; Yummy Jumiati Marsa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Naposo Nauli Bulung is a group of village youths and girls founded on custom, and the implementation of Naposo Nauli Bulung is in line with the Batak Mandailing custom. In an effort to preserve the culture of the Batak Mandailing, Hatobangon and Harajaon established Naposo Nauli Bulung so that traditional activities can be carried out with the presence of village youths and girls. Apart from that, Naposo Nauli Bulung also seeks to form and bring good changes for young people in Bangai Village, Torgamba District, South Labuhanbatu Regency. One of the efforts made by Naposo Nauli Bulung is to hold various kinds of educational, religious, even socio-cultural programs in order to achieve cultured, civilized and dignified youth. This study aims to identify and describe the role of Naposo Nauli Bulung in preserving the Batak Mandailing culture in Bangai Village, Torgamba District, South Labuhanbatu Regency. This research is a qualitative research with a case study type. In this study, there were 10 informants, namely the head of Bangai Village, the traditional leader (Harajaon) of Bangai Village, the traditional leader (Harajaon) of Sorik Village, the traditional leader (Harajaon) of Rasau Village, the traditional leader of Nauli Bulung, the local community and members of Naposo Nauli Bulung. feathers. The method used in this study is observation and interviews. The results of this study indicate that the role of Naposo Nauli Bulung in preserving Batak Mandailing culture aims to form attitudes and responsibilities towards Naposo Nauli Bulung, increase a sense of concern for the Mandailing community, assist in all activities in Marhorja traditional events and preserve local Batak Mandailing culture in Bangai Village Torgamba District, South Labuhanbatu Regency through the role of Naposo Nauli Bulung.